Tradisi Nyadran sebagai Simbol Perekat Ukhuwah Islamiah Di Desa Bleberan Playen Gunungkidul - Azka Musyhafiul Akhbab; Nafsan Azka Ahsani; Siti Rofiah; Ahmad Shofiyuddin Ichsan (IIQ An Nur Yogyakarta, 2023)
This research aimed to determine the Nyadran tradition as a symbol of the bond between Ukhuwah Islamiyah in Bleberan Playen, Gunungkidul, Yogyakarta. This research method used descriptive qualitative research with data collection using observation, interviews, and documentation. The research results showed that Nyadran was a tradition that has been carried out for a long time and doing tahlil before the nyadran begins was a sign that Bleberan people were still maintaining their ancestral heritage without leaving their religion. The community believed that Nyadran was a form of real practice in expressing gratitude to God as well as remembering and honouring. The nyadran carried out by the community turned out to had several Sufism values in their motives, some of which were found by researchers: gratitude, al-adl, at-repentance, and resignation. Although not directly shown in the process, these values did exist in nyadran and were a concrete form of the three main principles, namely hablum minallah (Relationship with God), hablum minannas (relationship with humans), and hablum minal'alam (relationship with nature)